2020
DOI: 10.1166/jctn.2020.9031
|View full text |Cite
|
Sign up to set email alerts
|

Feature Learning Approach for Facial Recognition Using Deep Metric Learning

Abstract: Standard deep learning in the context of facial recognition involves inputting a single image and outputting a label for that image. Deep metric learning distinguishes itself by outputting a real valued feature vector instead of a single label. The usage of deep metric learning has revolutionised facial recognition, making it very accurate and reliable. This paper exhibits the accuracy and reliability of the facial recognition model using deep metric learning in the application of an automated attendance syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…For the purpose of improving the efficiency of face recognition, Karkal G and other researchers built a non-invasive attendance system, which used CNN to detect faces and a neural network to recognize faces. The result showed that the system realized automatic detection of face recognition and improved the efficiency of attendance [11]. For the purpose of improving the efficiency of classroom attendance, Seelam V and others proposed an intelligent classroom attendance management system based on face recognition by using the principles of deep learning and computer vision.…”
Section: Related Workmentioning
confidence: 99%
“…For the purpose of improving the efficiency of face recognition, Karkal G and other researchers built a non-invasive attendance system, which used CNN to detect faces and a neural network to recognize faces. The result showed that the system realized automatic detection of face recognition and improved the efficiency of attendance [11]. For the purpose of improving the efficiency of classroom attendance, Seelam V and others proposed an intelligent classroom attendance management system based on face recognition by using the principles of deep learning and computer vision.…”
Section: Related Workmentioning
confidence: 99%